2016
DOI: 10.1074/jbc.m116.741637
|View full text |Cite
|
Sign up to set email alerts
|

Interdomain Conformational Changes Provide Allosteric Regulation en Route to Chorismate

Abstract: Multifunctional proteins play a variety of roles in metabolism.Here, we examine the catalytic function of the combined 3-deoxy-D-arabino heptulosonate-7-phosphate synthase (DAH7PS) and chorismate mutase (CM) from Geobacillus sp. DAH7PS operates at the start of the biosynthetic pathway for aromatic metabolites, whereas CM operates in a dedicated branch of the pathway for the biosynthesis of amino acids tyrosine and phenylalanine. In line with sequence predictions, the two catalytic functions are located in dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(91 citation statements)
references
References 51 publications
0
91
0
Order By: Relevance
“…Whereas type Ib contains a group of DAH7PS which has a discrete allosteric domain covalently linked to the catalytic barrel, such as the those from Thermotoga maritima 9 or Geobacillus sp ( Figure 1B). 10 The first fully characterized type II DAH7PS was from Mycobacterium tuberculosis (MtuDAH7PS, Figure 1C). 11,12 MtuDAH7PS contains both an N-terminal extension (three helices) and two other inserted helices to the core catalytic barrel, which constitute distinct allosteric binding sites specific to three different allosteric ligands (Trp, Phe and Tyr).…”
mentioning
confidence: 99%
“…Whereas type Ib contains a group of DAH7PS which has a discrete allosteric domain covalently linked to the catalytic barrel, such as the those from Thermotoga maritima 9 or Geobacillus sp ( Figure 1B). 10 The first fully characterized type II DAH7PS was from Mycobacterium tuberculosis (MtuDAH7PS, Figure 1C). 11,12 MtuDAH7PS contains both an N-terminal extension (three helices) and two other inserted helices to the core catalytic barrel, which constitute distinct allosteric binding sites specific to three different allosteric ligands (Trp, Phe and Tyr).…”
mentioning
confidence: 99%
“…The dimer offers opportunities for the future study of allostery and chorismate biosynthesis in Burkholderia as previously investigated for Geobacillus sp. (Nazmi et al, 2016) and Mycobacterium tuberculosis (Munack et al, 2016…”
Section: Resultsmentioning
confidence: 99%
“…In this species, DAHP synthase exists as a fusion protein with an N-terminal CM domain and is allosterically inhibited by prephenate, the product of CM. 107 SAXS studies revealed that a tighter association between the dimeric CM domains and the tetrameric DAHP synthase domains forms upon binding of prephenate, thus disrupting DAHP synthase function by occluding the active site. 107 Namely, Guinier analysis showed a subtle decrease in the radius of gyration R g from 36.5 ± 0.4 Å to 34.8 ± 0.6 Å in the presence of prephenate.…”
Section: Solution X-ray Scatteringmentioning
confidence: 99%
“…107 SAXS studies revealed that a tighter association between the dimeric CM domains and the tetrameric DAHP synthase domains forms upon binding of prephenate, thus disrupting DAHP synthase function by occluding the active site. 107 Namely, Guinier analysis showed a subtle decrease in the radius of gyration R g from 36.5 ± 0.4 Å to 34.8 ± 0.6 Å in the presence of prephenate. Evidence for compaction was also seen in the Kratky plots (Figure 5, blue to orange).…”
Section: Solution X-ray Scatteringmentioning
confidence: 99%
See 1 more Smart Citation